Dummy location selection algorithm based on location semantics and query probability - Jie WANG; Chunru WANG; Jianfeng MA; Hongtao LI (Tongxin xuebao)
Aiming at the problem of privacy leakage caused by attackers possessing background knowledge in traditional location privacy protection schemes,a dummy location selection algorithm based on location semantics and query probability was proposed.Under the conditions that the locations in the dummy location set satisfied semantic difference,similar query probability,and geographically dispersed,it avoided attackers who filter dummy locations by combining background knowledge,and the accuracy of query results was guaranteed.Simulation experiments verify that the proposed algorithm can effectively protect the user’s location privacy.